2021
DOI: 10.1088/1361-6544/ac13be
|View full text |Cite
|
Sign up to set email alerts
|

Transits close to the Lagrangian solutions L 1, L 2 in the elliptic restricted three-body problem

Abstract: In the last decades a peculiar family of solutions of the circular restricted three body problem has been used to explain the temporary captures of small bodies and spacecrafts by a planet of the Solar System. These solutions, which transit close to the Lagrangian points L 1, L 2 of the CRTBP, have been classified using the values of approximate local integrals and of the Jacobi constant. The use for small bodies of the Solar System requires to consider a hierarchical extens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…We believe that the results herein contribute significantly to the state-of-the-art in the literature. As implied in the introduction to this paper, exploring the dynamical properties of perturbations of the CR3BP has lately become a popular area of investigation in astrodynamics (refer to Jorba & Nicolás, 2020;Paez & Guzzo, 2021;Kumar et al, 2021) for just a few recent examples). This study, by outlining a simple and straightforward method for delineating transit and nontransit behavior within perturbed models, elegantly fills an important niche in this emerging topic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that the results herein contribute significantly to the state-of-the-art in the literature. As implied in the introduction to this paper, exploring the dynamical properties of perturbations of the CR3BP has lately become a popular area of investigation in astrodynamics (refer to Jorba & Nicolás, 2020;Paez & Guzzo, 2021;Kumar et al, 2021) for just a few recent examples). This study, by outlining a simple and straightforward method for delineating transit and nontransit behavior within perturbed models, elegantly fills an important niche in this emerging topic.…”
Section: Discussionmentioning
confidence: 99%
“…Prior investigations into models more complicated than the CR3BP have successfully found periodic and quasiperiodic orbits in the vicinity of former Lagrange points by employing single shooting or multiple shooting algorithms (Gómez et al, 2003;. Studies have found quasi-periodic orbits on the center manifolds of these dynamical replacements and have numerically demonstrated associated transit phenomena (Jorba & Nicolás, 2020;Paez & Guzzo, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The ERTBP is conveniently represented as a non-autonomous Hamiltonian system having the Lagrangian solutions L 1 , L 2 but without a global first integral, such as the Jacobi constant, which is used to define the Poincaré sections and label the halo orbits in the CRTBP. In the paper [28] we have introduced Floquet-Birkhoff normal forms for the ERTBP which allowed us to generalize and compute the families of planar and vertical Lyapunov orbits generating at L 1 , L 2 , as well as the low-energy transits from one side to the other of the secondary body. In this paper we compute halo orbits for the ERTBP from resonant Birkhoff-Floquet normal forms.…”
Section: Introductionmentioning
confidence: 99%
“…In the CR3BP the result is achieved by computing a resonant Birkhoff normal form of large order N : by neglecting the large order remainder, one remains with and integrable Hamiltonian system which is used to compute the Poincaré section of the Hamiltonian flow on the center manifold, and consequently the halo orbits. We extend these methods to the ERTBP by providing a definition of halo orbits in the elliptic problem, and a method of computation based on the resonant version of the Floquet-Birkhoff normal forms which were introduced in [28]. The resonant Floquet-Birkhoff normal forms will be used to define also the manifolds tubes and the transit motions associated to halo orbits in the ERTBP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation